Peningkatan Sikap Positif Matematis Siswa Melalui Pendekatan Matematika Realistik (PMR) - Siregar, Delisma; Surya, Edi; Fauzi, Kms. Muhammad Amin (Cybernetics: Journal Educational Research and Social Studies, 2024)
The purpose of this study was to determine: The aim of this research is to find out: 1) increasing students' positive attitudes towards mathematics through the Realistic Mathematics Approach. The main objective of this research is to determine the increase in students' positive attitudes towards mathematics with the Realistic Mathematics Approach (PMR). Apart from that, the process of solving positive attitude questions was also seen by students who were given a Realistic Mathematics Approach. Based on the results of research conducted by previous researchers, the average positive attitude gain score for students who were given the Realistic Mathematics Approach (PMR) was 0.523, higher than that of students who were given conventional learning, which was 0.388. The results of this research show that the average increase in positive attitudes of students who were given real learning was higher than students who were given regular learning.